Time-scale dynamics of proteome predicts the central carbon metabolism involved in triterpenoid accumulation responsive to nitrogen limitation in Ganoderma lucidum. Issue 4 (April 2021) - Lian, Danhong; Li, Lian; Liu, Xin; Zhong, Xin; Wang, Haizhen; Zhou, Sha; Gu, Li
Abstract: Central carbon metabolism describes the integration of transport pathway of main carbon sources inside the cell. Nitrogen (N) limitation is a favorable approach to stimulate ganoderic triterpenoid (GT) accumulation in  Ganoderma lucidum . In this study, the dynamic regulation of metabolism reassignment towards GT biosynthesis responsive to N limitation was investigated by iTRAQ-based proteome. Physiological data suggested that N limitation slightly affected cell growth but significantly enhanced GT contents in the initial 20 days. From day 10, the protein contents were halted by prolonged N limitation duration. Proteomics-based investigations revealed that the carbon skeletons integrated into GT precursors were regenerated by glycolysis and the tricarboxylic acid (TCA) cycle. Cells strategically reserved nitrogen by barely incorporating it into TCA cycle intermediates to form amino acids, and enzymes involved in protein degradation were up regulated. Furthermore, regulation of proteins in response to abiotic stress and oxidation– reduction processes played a critical role in maintaining cellular homeostasis. These findings indicated that the flux of carbon into GT following N deficiency was a consequence of the remodeling of intermediate metabolism in TCA cycle and glycolysis reactions. This study provides a rationale for genetic engineering of  G. lucidum, which may enable synchronized biomass and GT synthesis. Graphical abstract: Image 1 Highlights: Dynamic profiles of physiological parameters responsive to N limitati in Ganoderma lucidum were exhibited. A network of metabolism reassignment to GT was established through iTRAQ-based proteome. Central carbon metabolite promoted the formation of acetyl-CoA, possibly feeding GT biosynthesis.